2006
DOI: 10.1308/003588406x114730
|View full text |Cite
|
Sign up to set email alerts
|

Use of Icodextrin 4% Solution in the Prevention of Adhesion Formation Following General Surgery: From the Multicentre ARIEL Registry

Abstract: Icodextrin 4% solution can be used in a wide range of surgical procedures. In combination with good surgical technique, it may play an important role in adhesion reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 36 publications
1
56
0
13
Order By: Relevance
“…Moreover, the mean hydroxyproline level was significantly lower in the experimental animals in the 4% icodextrin treatment group compared to that in the control group. It has been reported that 4% icodextrin solution, which has been used as a peritoneal dialysis solution for a long time in the literature, reduces adhesion in the laparoscopic gynecological surgery (8), and prevents intraabdominal adhesions in the general surgery (23). Di Zerega et al (8) used icodextrin in their experimental study and reported that this solution less inhibited the phagocytic functions as compared to the solutions including glucose, and as well as less glycosylated the peritoneal proteins as compared to the glucose-based solutions.…”
Section: █ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the mean hydroxyproline level was significantly lower in the experimental animals in the 4% icodextrin treatment group compared to that in the control group. It has been reported that 4% icodextrin solution, which has been used as a peritoneal dialysis solution for a long time in the literature, reduces adhesion in the laparoscopic gynecological surgery (8), and prevents intraabdominal adhesions in the general surgery (23). Di Zerega et al (8) used icodextrin in their experimental study and reported that this solution less inhibited the phagocytic functions as compared to the solutions including glucose, and as well as less glycosylated the peritoneal proteins as compared to the glucose-based solutions.…”
Section: █ Discussionmentioning
confidence: 99%
“…Accordingly, they reported that adhesions were less frequently in the laparoscopic gynecologic surgery performed with icodextrin lavage. Moreover, multicenter ARIEL (Adept Registry for Clinical Evaluation) clinical studies reported that 4% icodextrin solution was useful to reduce adhesions following routine major abdominal surgeries (23).…”
Section: █ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conduction of 100 ml peritoneal lavage per 30 min during the operation and post-operative administration of 1000 ml to the peritoneal cavity is suggested for the clinical use of ID (9,10,12). To prevent intraabdominal adhesions, it is necessary to use 1500 ml ID for an adult patient undergoing an abdominal operation.…”
Section: Discussionmentioning
confidence: 99%
“…It persists for several days in the peritoneal cavity and is slowly absorbed by the lymphatic system into the systemic circulation, where it is broken down by amylase and metabolized to glucose (11). Several experimental and clinical studies have demonstrated the efficacy of ID in reducing postsurgical adhesion formation (11)(12)(13)(14)(15). In addition to these positive findings, the cheapness of the product is an advantage.…”
Section: Introductionmentioning
confidence: 99%